2009
DOI: 10.1016/j.immuni.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Lineage-Specific Transcriptional Networks Underscore Ikaros-Dependent Lymphoid Priming in Hematopoietic Stem Cells

Abstract: Summary Here we investigate the mechanisms that underlie the induction of developmental potential and establishment of cell fate during early hematopoiesis. A cascade of lineage-affiliated gene expression signatures, primed in hematopoietic stem cells (HSC) and differentially propagated in lineage-restricted progenitors, is identified. First evidence is provided for a stochastic sampling of lymphoid, erythroid and myeloid transcripts in HSC and multipotent progenitors (MPP). Multi-lineage priming is subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
247
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(260 citation statements)
references
References 88 publications
12
247
1
Order By: Relevance
“…In line with its capacity for multilineage differentiation, the HSC compartment is transcriptionally primed for genes engaged in erythroid, myeloid, and lymphoid differentiation ( Fig. 2; Mansson et al 2007;Ng et al 2009;Guo et al 2013;van Galen et al 2014). Transcriptional priming is defined by low levels of gene expression that are not yet functional and is frequently associated with restricted but not silent chromatin and with activity of factors that function as pioneers in lineage differentiation (Bernstein et al 2006;Mikkelsen et al 2007;Zaret and Carroll 2011).…”
Section: Priming Lymphoid Cell Identity and Repressing A Stem Cell Phmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with its capacity for multilineage differentiation, the HSC compartment is transcriptionally primed for genes engaged in erythroid, myeloid, and lymphoid differentiation ( Fig. 2; Mansson et al 2007;Ng et al 2009;Guo et al 2013;van Galen et al 2014). Transcriptional priming is defined by low levels of gene expression that are not yet functional and is frequently associated with restricted but not silent chromatin and with activity of factors that function as pioneers in lineage differentiation (Bernstein et al 2006;Mikkelsen et al 2007;Zaret and Carroll 2011).…”
Section: Priming Lymphoid Cell Identity and Repressing A Stem Cell Phmentioning
confidence: 99%
“…IKAROS is a key contributor to lymphoid lineage transcriptional priming in the HSC and its immediate progeny, the lympho-myeloid primed multipotent progenitor (LMPP) (Ng et al 2009). IKAROS-dependent transcriptional priming in the HSC and LMPP includes genes encoding membrane receptors and signaling factors such as the Il7r, Flt3, Cd79b, Notch1, Btla, Clnk, Ltb, and Ccr9, which are key regulators of early T-cell and B-cell differentiation (Fig.…”
Section: Priming Lymphoid Cell Identity and Repressing A Stem Cell Phmentioning
confidence: 99%
See 2 more Smart Citations
“…The apparent mechanism by which Ikaros controls DC development is through its regulation of a large panel of receptors and transcription factors. Although classically considered to be required only for the priming of lymphoid lineages, gene expression analysis of the earliest cell stages of hematopoietic development revealed that the loss of Ikaros affects the expression of large gene sets associated with both lymphoid and myeloid lineages [73]. For example, the expression of Flt3, IL-7 receptor, Notch1, and the transcription factor Mef2c are all controlled by Ikaros, suggesting that it acts globally on many aspects of lineage specification [74].…”
Section: Factors Regulating Early DC Progenitor Developmentmentioning
confidence: 99%